The value of metabolic surgery for patients with obesity and type 2 diabetes in Romania - Kovács, Gábor; Lorenzovici, László; Poiană, Cătălina; Catoi, Adriana Florinela; Duta, Ciprian; Timofte, Daniel Vasile; Coros, Marius Florin; Siménfalvi, Sándor; Farkas-Ráduly, Szabolcs; Török, Tamás; Jakab, Andrea Timea; Kacsó, Andrea; et al. (Frontiers in Nutrition, 2025)
BackgroundMetabolic surgery is a well-established intervention for managing severe obesity and type 2 diabetes, offering significant long-term health benefits. In Europe, procedures such as sleeve gastrectomy and Roux-en-Y gastric bypass have been shown to improve glycemic control, reduce obesity-related comorbidities, and enhance quality of life. Given the high prevalence of obesity in Romania, evaluating the cost-effectiveness of these surgical interventions is crucial for potential public funding inclusion.MethodsWe adapted a Central European type 2 diabetes—metabolic surgery cost-utility model using Romanian epidemiological and healthcare cost data to assess the cost-effectiveness of weight-loss surgery. The model incorporated three Body Mass Index strata (30–34.9, 35–39.9, ≥40 kg/m2) and tracked outcomes over a lifetime horizon. Cost and quality-adjusted life years were evaluated for sleeve gastrectomy and Roux-en-Y gastric bypass using two costing methodologies: Diagnosis-Related Group-based reimbursement and micro-costing analysis. Scenario analyses, including threshold analysis, were conducted to validate model robustness.ResultsObesity surgery was found to be a dominant strategy, yielding both cost savings and improved health outcomes across all Body Mass Index categories. The intervention led to increased life expectancy, reduced diabetes-related complications, and a significant reduction in healthcare costs. Even under conservative cost assumptions, the surgery remained cost-effective, with an Incremental Cost-Effectiveness Ratio (ICER) well within European funding thresholds.ConclusionThe results support the inclusion of metabolic surgery in Romania’s public healthcare system. Expanding access could reduce long-term healthcare expenditures while improving the quality of life for individuals with obesity and type 2 diabetes.